2020
DOI: 10.1007/s00381-020-04859-1
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes in adulthood after neurosurgical treatment of brain tumors in the first 3 years of life: long-term follow-up of a single consecutive institutional series of 97 patients

Abstract: Background Long-term outcome for children who underwent surgery for brain tumors in the first 3 years of life is not wellknown. Methods We performed a retrospective study on surgical morbidity, mortality rate, academic achievement, and work participation in children below 3 years of age who underwent primary tumor resection for a brain tumor in the period from 1973 to 1998. Gross motor function and activities of daily life were scored according to the Barthel Index. Long-term survivors were defined as with a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Dear Editor, We compliment Lundar et al [1] on their important report of functional outcomes more than 20 years after treatment of neurosurgical treatment of brain tumors in the 1st 3 years of life. Pillai et al [2] reported a somewhat similar assessment of functional outcomes in children treated for brain tumors in the first year of life, followed for a minimum of 5 years after surgery.…”
mentioning
confidence: 76%
See 1 more Smart Citation
“…Dear Editor, We compliment Lundar et al [1] on their important report of functional outcomes more than 20 years after treatment of neurosurgical treatment of brain tumors in the 1st 3 years of life. Pillai et al [2] reported a somewhat similar assessment of functional outcomes in children treated for brain tumors in the first year of life, followed for a minimum of 5 years after surgery.…”
mentioning
confidence: 76%
“…We were surprised and disappointed that Lundar et al [1] omitted to cite this report, which is one of the most pertinent to their study. Indeed, on a PubMed search for "long-term outcomes after brain tumor in infants," this article by Pillai et al [2] came up as #6 when using the "best match" display option.…”
mentioning
confidence: 92%
“…We thank Steinbok and Pillai for their response to our paper "Outcomes in adulthood after neurosurgical treatment of brain tumors in the first 3 years of life: long-term follow-up of a single consecutive institutional series of 97 patients" [1]. They express compliments but also regret that their paper from 2012 was not listed in our references [2].…”
Section: Dear Editormentioning
confidence: 98%
“…In a study investigating the remote outcome in survivors who reached adulthood [91], it was found that 33% of patients with high grade tumors became long-term survivors in contrast to 20-year survival rate of 82% in patients with low grade tumors. Regarding the clinical and functional outcome of high-grade lesions group of patients, it was reported that most of them were affected by severe late effects of radiotherapy given in their first year of life including second neoplasms, cerebrovascular disease, and coronary valvular disease, and three died at the age of 29, 30, and 41 years.…”
Section: Outcome Prognosismentioning
confidence: 99%